Marine fishes from Galicia (NW Spain): an updated checklist - Bañon, Rafael; Villegas-Ríos, David; Serrano, Alberto; Mucientes, Gonzalo; Arronte, Juan Carlos (Zootaxa, 2010)
An annotated checklist of the marine fishes from Galician waters is presented. The list is based on historical both literature records and on new revisions. The ichthyofauna list is composed by 398 species. It is diversified in 2 superclasses, 3 class, 35 orders, 139 families and 288 genuses. Perciformes is the most diverse order with 37 families, 91 genus and 136 species. Gobiidae (19 species) and Sparidae (19 species) are the richest families. Biogeographically, the Lusitanian is the most important group including 204 species (51.3%), followed by the Atlantic group with 149 species (37.4%), the Boreal group with 28 species (7%) and the 17 species (4.3%) of the African group. A total of 42 species have been included as new records for the study area, and 3 records have been identified as doubtful. Identification and registration of errors from previous studies have been also indicated.